A NIGHT IN THE LIFE OF AN OR NURSE - Laukkanen, Cindy (Operating Room Nurses Association of Canada Journal, 2005)
The author shares a personal experience, during a night shift in the OR, that changed her forever. I was defined as a nurse by that moment of trauma. I spent 9 years as a trauma specialist in a large US hospital. We did gun shots and stabbings every single night. After facing the results of too many school shootings, I came back to Canada. I was tired. After that night, death was never again an idea, a poetic notion of the spirit leaving the body. It was cold, it was pulseless, it was bloody, and it has a smell all it’s own. To this day I can tell if a patient is going to die on the table, I can smell it. I had faced fear and death, and survived. I was certainly not “new” anymore... nor was I naïve.